Atributos físicos de latossolo vermelho sob pousio ou cultivado com forrageiras tropicais sob pastejo - Castagnara, Deise Dalazen; Karwatte Junior, Nivaldo; Zoz, Tiago [UNESP]; Piano, Jeferson Tiago; Rossol, Charles Douglas; Rabello de Oliveira, Paulo Sergio; Seidel, Edleusa Pereira (Universidade Federal de Uberlândia (UFU), 2012)
The objective was to study the physical attributes of an Oxisol under fallow or planted with tropical grasses under grazing. The experiment was conducted under the experimental design of randomized blocks in split-plot 2 x 5, being five types of use of soil (Brachiaria ruziziensis, Panicum maximum cv. Aries, Brachiaria brizantha cv. MG5, Panicum maximum cv. Mombaca and fallow) and two evaluation periods (after the first and after the second grazing), with four replications. We evaluated the characteristics of soil bulk density, total porosity, microporosity and macroporosity, after the first and second grazing, and soil resistance to penetration after the second grazing. In layer of 0.00 to 0.10 m, the macroporosity was affected by the interaction between types of use and evaluation periods, while the microporosity and total porosity were reduced and the density was increased from first to second evaluation time. In the subsurface layer (0.10-0.20 m), there were significant effect only of evaluation time, on the macroporosity, total porosity and density. The porosity were reduced, while the density increased from first to second evaluation time. No significant effects of types of use of soil on penetration resistance in all layers studied. The maintenance of an Oxisol under fallow or cultivation with tropical grasses subjected to grazing cattle causes a reduction in total porosity and increased density of surface soil layers (0 to 0.10 m) and subsurface (0.10 - 0.20 m), without promoting changes on resistance to penetration mechanics.

Objetivou-se estudar os atributos físicos de um Latossolo Vermelho sob pousio ou cultivado com gramíneas tropicais sob pastejo. O experimento foi conduzido sob o delineamento experimental em blocos casualizados, em esquema de parcelas subdivididas 5 x 2, sendo cinco tipos de uso do solo (Brachiaria ruziziensis, Panicum maximum cv. Áries, Brachiaria brizantha cv. MG5, Panicum maximum cv. Mombaça e pousio) e duas épocas de avaliação (após o primeiro e após o segundo pastejo), em quatro repetições. Foram avaliadas as características de densidade do solo, porosidade total, microporosidade e macroporosidade, após o primeiro e segundo pastejo, e a resistência do solo à penetração após o segundo pastejo. Na camada de 0,00-0,10 m, a macroporosidade foi afetada pela interação tipo de uso do solo e época de avaliação, enquanto a microporosidade e porosidade total foram reduzidas e a densidade foi aumentada da primeira para a segunda época de avaliação. Na camada subsuperficial (0,10-0,20 m), houve significância apenas para a macroporosidade, porosidade total e densidade. A macroporosidade e porosidade total sofreram redução, enquanto a densidade aumentou da primeira para a segunda época de avaliação. Não houve efeito significativo dos tipos de uso do solo sobre a resistência à penetração em todas as camadas estudadas. A manutenção de um Latossolo Vermelho sob pousio ou seu cultivo com gramíneas tropicais submetidas ao pastejo de bovinos ocasiona redução na porosidade total e aumento na densidade do solo nas camadas superficial (0-0,10 m) e sub-superficial (0,10-0,20 m), sem promover alterações sobre a resistência do solo à penetração mecânica.
Physical attributes of oxisol under fallow or cultivated with tropical forages under grazing
Keywords: Soil bulk density; Porosity; Resistance to penetration